FAKTOR- FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN SUSTAINABILITY PERFORMANCE (Studi pada website perusahaan manufaktur terdaftar di Bursa Efek Indonesia tahun 2011) - Maulida, Ken Auva; Adam, Helmy (Jurnal Ilmiah Mahasiswa FEB, 2013)
The objectives of this research was to examine the influence of leverage ratio, profitability ratio, public ownership proportion, and firm size to the disclosure of sustainability performance on companies website which was listed at Indonesia Stock Exchange until 2011. The population that have been use in this research was all the companies that have been listed in Indonesia Stock Exchange, the research periode of this research was 2011. Sustainability performance measured by sustainability performance disclosure index, based on item indicator from GRI G3 Guideline. Data processing and analysis is based on multiple linier regression model. The result of multiple linier regression analysis indicate that firm size has a statistically significant positive relationship with the disclosure of sustainability performance on company website in the other hand leverage ratio has a statistically significant negative relationship. Profitability ratio, public ownership proportion do not have significant influence. Keyword: sustainability performance disclosure, firm size, profitability, leverage, public ownership proportion